Implementation of Value-Based Management in Shaping Character at Madrasah - Rida Rahayu Akhirul Banat; Muhammad Fadli; Fatkhur Rohman (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research focuses on the study of the implementation of Value Based Management in character building of students at MTs Negeri 2 Asahan thru stages of value mindset, value analysis, and continuous value implementation. This is due to the emergence of moral degradation issues in the school environment, as seen from the increase in undisciplined behavior, weak social concern, low sense of responsibility, and decreased ethical awareness among students. Therefore, educational institutions can no longer emphasize academic achievement alone but need to build a learning system that places values as the main foundation for character development of students. The research employs a descriptive qualitative approach with a phenomenological method conducted at MTs Negeri 2 Asahan, Asahan Regency, North Sumatra. Data collection was carried out thru participatory observation, in-depth interviews, and documentation involving the head of the madrasa, deputy head of the madrasa, teachers, educational staff, and students as sources of information. The data were then analyzed thru a structured process of reduction, presentation, and conclusion drawing to ensure that the research results comprehensively depict the field conditions. The research results show that the implementation of Value-Based Management at MTs Negeri 2 Asahan has been carried out systematically and integrated into all educational activities, starting from the formation of a shared awareness thru the instillation of religious values, discipline, honesty, and responsibility as the foundation of the madrasah culture. This is followed by the process of identifying the gap between ideal values and the actual behavior of students, which is influenced by family conditions, social environment, and differences in student character. The implementation of values is realized thru the integration of character education in learning activities, student programs, counseling services, and point-based disciplinary rules. Thus, this research emphasizes that Value-Based Management is capable of shaping students' character comprehensively thru the application of values integrated into the educational organization's culture.